Kegiatan Bimbingan Belajar (Bimbel) Bahasa Inggris dan Matematika untuk Siswa Sd di Lingkungan rt. 29 rw. 10 Kelurahan 20 Ilir d.iv Kota Palembang - Muhammad Bambang Purwanto; Sherly Malini (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity aims to improve the quality of education through tutoring activities and activate the activities of students who are domiciled in IR Limas Jaya, RT. 29, RW.10 Kelurahan 20 Ilir D IV, Ilir Timur District 1 Palembang City. along with undergraduate graduates who have a lot of free time in the afternoon. Tutoring activities are carried out in the courtyard of the Al-Munawarroh Mosque. This activity lasted for 16 meetings with material for the SD/MI level and the material provided was adjusted to the student's needs (conditionally). The time for tutoring activities is Monday – Thursday from 15.00 WIB to 17.00 WIB. The teachers (tutors) guide students in doing school assignments (PR) and teach students about materials that have not been understood during learning at school. The material taught focuses on English and mathematics lessons. The lecturers in this activity are lecturers from the Darussalam Polytechnic who are assisted by 4th semester students of the Darussalam Polytechnic. The learning method used is the lecture and discussion method. BIMBEL activities are held 2 times a week for a maximum of 3 hours discussing enrichment material related to the material being taught by teachers at school.